DISTRIBUSI MONYET HITAM SULAWESI (Macaca nigra) di KECAMATAN PINOLOSIAN, KECAMATAN PINOLOSIAN TENGAH dan KECAMATAN BOLAANG UKI - Eunike V.Panggalo Panggalo; J.S. Tasirin; Euis F.S. Pangemanan (COCOS, 2018)
ABSTRACT   Macaca nigra is one of the macaca species on the island of Sulawesi. There are 8 types of macaca on the island of Sulawesi, namely M. nigra, M. hecki, M. nigrescens, M. maura, M. ocrheata, M. tongkeana, M. brunescens, M. togeaus (Nowak, 1999). The study was carried out in the buffer zone of Bogani Nani Wartabone Natural Landscape, South Bolaang Mongondow, North Sulawesi with the aim of finding out the distribution of M. nigra in Pinolosian sub-district, sub-districts of Central Pinolosian and Bolaang Uki sub-district by using a camera trap. 37 camera traps were installed scattered in the Pinolosian sub-district, sub-district Central Pinolosian and Bolaang Uki sub-district for three months. What is observed is how much M. nigra passes through the camera trap.   The result showed that highest level encounter M. nigra found in sub-district Central Pinolosian while in  Bolaang Uki sub-districtwas foundM. nigra. The level of encounter in forest land cover types and APL has no difference. The level of encounter in the closest area of Bogani Nani Wartabone National Park has a high level of encounter on the middle distance. Keywords: Macaca nigra, Camera Trap, Encounter Rate, Roaming Area.